Erector Spinae Plane Block in Abdominal Surgery: A Meta-Analysis - Viderman, Dmitriy; Aubakirova, Mina; Abdildin, Yerkin G. (Frontiers in Medicine, 2022)
Background Abdominal surgery is one of the most definitive and mainstay treatment options for adnominal pathologies in clinical practice. Acute postoperative pain is a major challenge in the postoperative period. Uncontrolled pain may result in serious complications. Although opioids are commonly used for analgesia after major abdominal surgeries, they can lead to side effects, such as nausea and vomiting, constipation, pruritus, and life-threatening respiratory depression. Regional anesthetic techniques are commonly used to improve pain management prevent or minimize these side effects. The objective of this meta-analysis is to assess the effectiveness of erector spinae plane block (ESPB) and standard medical (no block) pain management after major abdominal surgeries. Methods We searched for articles reporting the results of randomized controlled trials on ESPB and no block in pain control published before May 2021. Results The systematic search initially yielded 56 publications, 49 articles were excluded, and seven randomized clinical trials were included and analyzed. We extracted the data on postoperative opioid consumption, the efficacy of pain relieve, time to the first opioid demand, and the rate of postoperative complications in the ESPB group and no block group. Conclusions Opioid requirement and time to first analgesic request was significantly reduced in ultrasound-guided ESPB group, but pain scores, nausea and vomiting did not differ significantly after pooling the results of the block and no block studies. There were no reports on serious complications related to ESPB.